Cut-Offs for Disease Activity States in Axial Spondyloarthritis With Ankylosing Spondylitis Disease Activity Score (ASDAS) Based on C-Reactive Protein and ASDAS Based on Erythrocyte Sedimentation Rate: Are They Interchangeable? - Georgiadis, Stylianos; Ørnbjerg, Lykke Midtbøll; Michelsen, Brigitte; Kvien, Tore K; Di Giuseppe, Daniela; Wallman, Johan K; Závada, Jakub; Provan, Sella A; Kristianslund, Eirik Klami; Rodrigues, Ana Maria; Santos, Maria José; Rotar, Žiga; et al. (The Journal of rheumatology, 2024)
OBJECTIVE: Ankylosing Spondylitis Disease Activity Score based on C-reactive protein (ASDAS-CRP) is recommended over ASDAS based on erythrocyte sedimentation rate (ASDAS-ESR) to assess disease activity in axial spondyloarthritis (axSpA). Although ASDAS-CRP and ASDAS-ESR are not interchangeable, the same disease activity cut-offs are used for both. We aimed to estimate optimal ASDAS-ESR values corresponding to the established ASDAS-CRP cut-offs (1.3, 2.1, and 3.5) and investigate the potential improvement of level of agreement between ASDAS-ESR and ASDAS-CRP disease activity states when applying these estimated cut-offs. METHODS: We used data from patients with axSpA from 9 European registries initiating a tumor necrosis factor inhibitor. ASDAS-ESR cut-offs were estimated using the Youden index. The level of agreement between ASDAS-ESR and ASDAS-CRP disease activity states was compared against each other. RESULTS: In 3664 patients, mean ASDAS-CRP was higher than ASDAS-ESR at both baseline (3.6 and 3.4, respectively) and aggregated follow-up at 6, 12, or 24 months (1.9 and 1.8, respectively). The estimated ASDAS-ESR values corresponding to the established ASDAS-CRP cut-offs were 1.4, 1.9, and 3.3. By applying these cut-offs, the proportion of discordance between disease activity states according to ASDAS-ESR and ASDAS-CRP decreased from 22.93% to 19.81% in baseline data but increased from 27.17% to 28.94% in follow-up data. CONCLUSION: We estimated the optimal ASDAS-ESR values corresponding to the established ASDAS-CRP cut-off values. However, applying the estimated cut-offs did not increase the level of agreement between ASDAS-ESR and ASDAS-CRP disease activity states to a relevant degree. Our findings did not provide evidence to reject the established cut-off values for ASDAS-ESR.
Keywords: krevní sedimentace; C-Reactive Protein; stupeň závažnosti nemoci; registry data; axiální spondyloartritida; C-reaktivní protein; Middle Aged; registrace; mužské pohlaví; Blood Sedimentation; Adult; axial spondyloarthritis; Registries; ankylózující spondylitida; ženské pohlaví; Spondylitis, Ankylosing; Humans; validation study; lidé středního věku; patient outcome assessment; dospělí; Axial Spondyloarthritis; Female; Severity of Illness Index; lidé; Male